2017
DOI: 10.3126/jnhrc.v15i1.18009
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage Rate of Methicillin Resistant Staphylococcus aureus among Health Care Workers at a Tertiary Care Hospital in Kathmandu, Nepal

Abstract: . Mannitol salt agar was used to culture the nasal swabs. Antimicrobial susceptibility testing was performed by KirbyBauer disc diffusion technique following Clinical and Laboratory Standards Institute guidelines. Methicillin-resistant Staphylococcus aureus strains were confirmed by using cefoxitin disc and by determining the minimum inhibitory concentration of oxacillin by agar dilution method. Results:Of 252 healthcare workers, 46(18.3%) were positive for Staphylococcus aureus among which 19(41.3%) were Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 10 publications
8
26
2
Order By: Relevance
“…To our best knowledge, five studies from Nepal characterized MRSA in hospital settings obtained from both, patients or healthcare workers (Ansari et al, 2014; Pahadi et al, 2014; Shrestha et al, 2014; Pokhrel et al, 2016; Khatri et al, 2017). Isolation rates varied from 14.6 to 69%.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, five studies from Nepal characterized MRSA in hospital settings obtained from both, patients or healthcare workers (Ansari et al, 2014; Pahadi et al, 2014; Shrestha et al, 2014; Pokhrel et al, 2016; Khatri et al, 2017). Isolation rates varied from 14.6 to 69%.…”
Section: Introductionmentioning
confidence: 99%
“…Khatri S et al also found MRSA nasal carriage in highest proportion in lab technicians 10.5% followed by nurses 9.9% like our study. 24 El-Aila NA et al found highest prevalence of MRSA among nurses (30.4%), after that in doctors (16%). 25 Shibabaw A et al also found highest MRSA prevalence among nurses.…”
Section: Discussionmentioning
confidence: 94%
“…Khatri S et al and El-Aila NA et al also found vancomycin 100% sensitive for MRSA and MSSA and oxacillin 100% resistant for MRSA and 100% sensitive for MSSA. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Chloramphenicol, co-trimoxazole and ciprofloxacin were much sensitive drugs in our study with statistical significance (p<0.05). Khatri et al (2017) reported that higher MRSA sensitive to vancomycin followed by co-trimoxazole (84.2%) [24].…”
Section: Discussionmentioning
confidence: 99%